Community-Based Tourism Transformation: What Does The Local Community Need? - Adi Suryani; Soedarso Soedarso; Deti Rahmawati; Endarko Endarko; Achmad Muklason; Berto Mulia Wibawa; Siti Zahrok (IPTEK Journal of Proceedings Series, 2020)
Tourism is a promising development sector. It has strong potentials for improving local community life quality by alleviating poverty, broadening information access, improving facilities and infrastructure, opening new and diversifying employment. Thus, today tourism is recognized as one of key sectors in development possessing multiplier effects on other sectors and contributing to other development goals attainment. This encourages many communities to initiate and run their local-scale tourism at their kampung. The development of these community-based tourisms need to be strengthened by community capacity to develop their tourism into more sustainable and competitive destinations. Moreover, the Covid-19 pandemic potentially threatens tourism existence and sustainability, especially if the communities do not rapidly respond by improving their tourism capacities. This study aims to explore several factors needed by local community to foster tourism transformation. The study is concentrated on examining WPP Dalegan and Dalegan community tourism transformation needs. The data are collected through community dialog incorporated with community service program. The study identifies three primary transformation elements for fostering WPP tourism improvement. The first factor is transformational and collective community leader who provides empowerment, climate and chance for Dalegan community to participate and orients to community social changes. The second factor is Dalegan community capacity building. Dalegan tourism transformation rests on its local community to learn together and improve the quality of their tourism services and products. The third factor is development facilitation. To successfully transform, Dalegan community needs to expand their networking, build horizontal and vertical partnerships.